Teaching the Concepts of the Mechanical Properties of Materials in Conservation - W. (Bill) Wei (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Questions concerning the mechanical properties and the mechanical testing of materials come up often in conservation practice. However, the engineering concepts of mechanical properties do not generally appear in conservation training curricula, where chemistry, and to some extent, physics, dominate the training in the natural sciences. Over the past decade, the RCE has developed a one to two day workshop on the subject as part of the basic science curricula in two conservationtraining programs. It provides conservation students with the background to deal with basic issues of the strength of materials and adhesives in their work. The workshop is based on two concepts: 1) teaching the “foreign” technical language of mechanical properties and relating that to everyday laymen’s terms, and 2) having students perform simple mechanical tests which can eventually be used in the conservation studio, without the need for complex and expensive equipment.